Uganda : 2019 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Uganda. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2019)
This 2019 Article IV Consultation discusses that Uganda has made impressive development gains and achieved the Millennium Development Goal on halving poverty ahead of schedule. However, going forward, Uganda must create over 600,000 jobs per year to keep up with its growing population, while making further progress on poverty reduction and the Sustainable Development Goals. The authorities' development strategy centers on infrastructure and a nascent oil sector. If investments proceed as planned, growth could range between 6 and 7 percent over the next five years. It is important to adopt an effective fiscal anchor and strengthen the budget process to become more binding for fiscal outcomes. It is also recommended to support human capital development and make growth more inclusive by improving the efficiency of public services and providing adequate budget allocations for social sectors. The consultation also suggests strengthening implementation and institutions of the governance and anti-corruption framework. Ensure that the Anti-Money Laundering/Countering the Financing of Terrorism regime is brought in line with international standards.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet